A biological invasion impacts ecosystem services: cane toads change the rate of scavenging and the suite of scavengers. Issue 5 (11th May 2021) - Pettit, Lachlan; Ward‐Fear, Georgia; Shine, Richard
Abstract: By affecting the abundance of key native species, invasive taxa may disrupt ecosystem services. In Australia, large monitor lizards ( Varanus spp.) play critical roles as scavengers and apex predators. Our broadscale surveys (across two transects, 1300 and 2500 km) show that in tropical areas where the arrival of fatally toxic cane toads ( Rhinella marina ) has massively reduced the abundance of monitors ( Varanus panoptes ), rates of removal of deployed baits are more than halved, and the assemblages of scavengers are dominated by birds or mammals rather than reptiles. In contrast, populations of another monitor species in eastern Australia ( Varanus varius ) were little affected by toad arrival, as were scavenging rates and assemblages. The mechanisms responsible for those shifts, and their consequences on ecosystem services, warrant further research.